Training on The Utilization of Coconut Water Into Nata De Coco A Food Product With High Fiber Content in Communities in Nagari Tanjung Balik, Solok District - Advinda, Linda; Irdawati, Irdawati; Syahrastani, Syahrastani; Rahmi, Elva; Larashinda, Mentari (Fakultas MIPA Universitas Negeri Padang, 2024)
The use of coconut water by the community is still rarely done, even though coconut water can be used as a basic ingredient for making nata de coco. Nata de coco is a processed product that is quite popular in Indonesia. The aim of the service activity is to provide training in making nata de coco to PKK women in Nagari Tanjung Balik, Solok District. Training on making nata de coco was carried out considering that PKK women in Nagari Tanjung Balik really need knowledge and skills that can be used as provisions to start a business. The training provided starts with an introduction to nata de coco seeds, the manufacturing process, and packaging nata de coco. After receiving training, participants who initially did not know about nata de coco became aware of it and were able to produce nata de coco.